2021
DOI: 10.1016/j.snb.2020.128948
|View full text |Cite
|
Sign up to set email alerts
|

Wireless wearable wristband for continuous sweat pH monitoring

Abstract: Several studies have shown that the determination of pH in sweat, which is one of the most accessible body fluids, can be an indicator of health and wellness, and even be used for potential disease diagnosis. On that basis, we present herein a wearable wristband for continuous and wireless monitoring of sweat pH with potential applications in the field of personal health assessment. The developed wristband consists of two main parts: a microfluidic cloth analytical device (μCAD) to collect continuously the swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…sleep trackers [90]; fertility and pregnancy trackers [91]; and monitors for respiration [92], blood pressure [93][94][95][96], pH [97,98], stress [99], mood [100], and sleep [101].…”
Section: Embedded Medical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…sleep trackers [90]; fertility and pregnancy trackers [91]; and monitors for respiration [92], blood pressure [93][94][95][96], pH [97,98], stress [99], mood [100], and sleep [101].…”
Section: Embedded Medical Devicesmentioning
confidence: 99%
“…Examples include smart watches [ 83 , 84 ] that can monitor heart rate, blood glucose level, blood pressure, and breathing rate. Other fitness and health improvement wearables include temperature sensors [ 85 , 86 ]; pulse oximeter SpO [ 87 , 88 , 89 ]; sleep trackers [ 90 ]; fertility and pregnancy trackers [ 91 ]; and monitors for respiration [ 92 ], blood pressure [ 93 , 94 , 95 , 96 ], pH [ 97 , 98 ], stress [ 99 ], mood [ 100 ], and sleep [ 101 ].…”
Section: Kpis For Specific 5g-healthcare Use Casesmentioning
confidence: 99%
“…It largely uses body fluid samples such as sweat for the point-of-care diagnosis of diseases and certain laboratory tests. A microfluidic device can be sorted into the mechanism of active micropumps [ 127 , 128 ] and passive micropumps [ 129 , 130 , 131 , 132 , 133 ]. An active micropump requires an external power source to guide a continuous fluid flow with an adjustable flow rate into a microchannel.…”
Section: Sweat-sensing Device (Ssd)mentioning
confidence: 99%
“…[139] Colorimetric sensors can be fabricated on different wearable substrates, such as paper, [140] hydrogel, [141] fiber, [142] fabric, [143] and yarn. [133,134] Wearable colorimetric devices include onskin platform, [135,144,145] smart band, [143] wristband, [146] contact lenses, [138] T-shirt, [133] etc., and are usually used to detect human sweat, [136,137,143] tears, [138] VOCs, [134] UV, [147] etc. Kim et al [134] demonstrated an eye-readable and wearable H 2 S sensing platform based on colorimetric dye-loaded nanofiber yarn, which could be incorporated into a worker's garment as a visual indicator; and was adequate for inexpensive mass-production (Figure 7A).…”
Section: (9 Of 20)mentioning
confidence: 99%
“…To enrich the scope of applications, colorimetric detection can be combined with other detection mechanisms or technologies into smart wearable devices. [136,[144][145][146]148] Xu et al [148] reported a resistive and colorimetric dual-mode device, in which the reduced graphene oxide (rGO)/PDMS worked as a highly sensitive semi-conductor and the colloidal crystal films worked as colorimetric substance to detect the subtle and large human motions, respectively (Figure 7E). Combining a thermal sensing module for sweat monitoring with a BLE module for wireless data transmission, Kwon et al [144] fabricated a wireless platform for the real-time analysis of sweat rate and skin temperature (Figure 7F).…”
Section: (9 Of 20)mentioning
confidence: 99%